Early Main Group Metal Catalysis: How Important is the Metal? - Penafiel, Johanne; Maron, Laurent; Harder, Sjoerd (Angewandte Chemie International Edition, 2015)
Organocalcium compounds have been reported as efficient catalysts for various alkene transformations. In contrast to transition metal catalysis, the alkenes are not activated by metal-alkene orbital interactions. Instead it is proposed that alkene activation proceeds through an electrostatic interaction with a Lewis acidic Ca2+. The role of the metal was evaluated by a study using the metal-free catalysts: [Ph2N-][Me4N+] and [Ph3C-][Me4N+]. These naked amides and carbanions can act as catalysts in the conversion of activated double bonds (CO and CN) in the hydroamination of ArNCO and RNCNR (R=alkyl) by Ph2NH. For the intramolecular hydroamination of unactivated CC bonds in H2CCHCH2CPh2CH2NH2 the presence of a metal cation is crucial. A new type of hybrid catalyst consisting of a strong organic Schwesinger base and a simple metal salt can act as catalyst for the intramolecular alkene hydroamination. The influence of the cation in catalysis is further evaluated by a DFT study.
Keywords: homogeneous catalysis; main group metals; hydroamination; Schwesinger base